Estudo da remoção de Azocorantes por hidróxidos duplos Lamelares - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The increasing consumption of dyes by the paper, cosmetics, food, leather and textile industries has generated great environmental concern due to the disposal of effluents to the environment. The azodyes belong to the class of textile dyes that when released to the environment without the due treatment can form toxic subproducts, hinder biological processes and among others. In an attempt to contain the environmental problem, we have studied alternatives for the dye removal process, such as adsorption, photodegradation and oxidative processes. In this context, layered double hydroxides (LDH), also known as anionic clays present as a potential adsorbent for the removal of dyes in aqueous solution. This work aims to study the removal of azo dyes in individual solutions and dyes mixtures using layered double hydroxides derived from Mg/Al and Zn/Al, synthesized by the co-precipitation method, in molar ratio 2:1. The compounds were characterized by FTIR spectra, thermogravimetric analyses, diffraction X-ray and scanning electron microscopy (SEM). The calcined LDH were used to remove methyl orange, Congo red, and remazol black dyes in individual solutions and in a dyes mixture at different concentrations. The results indicate that for individual dyes removal in aqueous solutions LDH Zn/Al exhibits greater adsorptive capacity dyes when compared to LDH Mg/Al. However, for the removal of the dye mixture LDH Mg/Al showed higher values of adsorptive capacity with qe around 2211.3 mg g-1 . X-ray diffraction analysis of the LDH recovered after removal indicates the reconstruction of the lamellar structure. The LDH used for the removal of the methyl orange dye showed characteristic peaks of intercalation in their pattern, which is also observed in the LDH used for the removal of the dye mixture, which suggests an adsorption selectivity in a mixture. The adsorption isotherms of the kinetics of removal indicate that the Langmuir model best describes the dye removal/adsorption system.
Keywords: Corantes; Corantes têxteis; Azocorantes; Azo corantes; Hidrotalcitas; Adsorventes; Azodyes; Hydrotalcite; Adsorbents; CIENCIAS EXATAS E DA TERRA::QUIMICA